2018
DOI: 10.3389/fpls.2018.00701
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Transfer From Bacteria and Plants to the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis

Abstract: Arbuscular mycorrhizal fungi (AMF) belong to Glomeromycotina, and are mutualistic symbionts of many land plants. Associated bacteria accompany AMF during their lifecycle to establish a robust tripartite association consisting of fungi, plants and bacteria. Physical association among this trinity provides possibilities for the exchange of genetic materials. However, very few horizontal gene transfer (HGT) from bacteria or plants to AMF has been reported yet. In this study, we complement existing algorithms by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 100 publications
(130 reference statements)
1
57
0
Order By: Relevance
“…Thomas A. Richards et al defined 14 candidate plant-fungi HGT events by phylogenomic analysis, nine of which showed an infrequent pattern of HGT between plants and fungi, and some kind of genes were involved in transport of the sugar L-fucose and other functions [79]. Meng Li et al identified 19 fungal genes that had been transferred between fungi and bacteria/plants, which suggests that HGT might have played a role in the evolution and symbiotic adaptation of this arbuscular mycorrhizal fungus [80]. However, due to the incomplete assembly of the sydowii H-1.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas A. Richards et al defined 14 candidate plant-fungi HGT events by phylogenomic analysis, nine of which showed an infrequent pattern of HGT between plants and fungi, and some kind of genes were involved in transport of the sugar L-fucose and other functions [79]. Meng Li et al identified 19 fungal genes that had been transferred between fungi and bacteria/plants, which suggests that HGT might have played a role in the evolution and symbiotic adaptation of this arbuscular mycorrhizal fungus [80]. However, due to the incomplete assembly of the sydowii H-1.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence relatedness between land plants and Mucoromycota might have resulted from several scenarios, including differential gene losses and organellar origin. On the other hand, it is also likely that PpMACRO2 was acquired from mycorrhizae-like fungi by the common ancestor of land plants 63 . This second scenario is not only consistent with the common belief that physical association, such as symbiosis, often facilitates horizontal gene transfer (HGT), but also supported by the amino acid residues uniquely shared by Mucoromycota and bryophyte sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal gene transfer (HGT) has long been recognized as an important force in the evolution of organisms (30). HGT occurs among different bacteria and plays important roles in the adaptation of microorganisms to different hosts or environmental conditions (31). More and more evidence for gene transfer between distantly related eukaryotic groups has been presented (30).…”
Section: Discussionmentioning
confidence: 99%